Superfine fiber composite battery diaphragm and preparation method thereof

By using polypropylene meltblown fiber material and combining hot rolling, drafting, plasma treatment and coating finishing technologies, a microfiber composite battery separator was prepared, solving the problems of insufficient thermal stability and porosity of the existing separator, and achieving efficient electrochemical performance and long-life lithium-ion batteries.

CN119581788APending Publication Date: 2025-03-07HENAN INST OF ENG
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411868748.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The existing polyolefin battery separators are prone to heat shrinkage when the temperature is high, resulting in battery short circuit and fire risks. The porosity and liquid absorption rate are low, limiting the battery's charge and discharge cycle performance and life.

Method used

The low-cost polypropylene meltblown fiber material is used as the substrate to prepare the microfiber composite battery separator through hot rolling, drafting, plasma treatment and coating finishing to improve its porosity and liquid absorption.

Benefits of technology

The prepared microfiber composite battery separator has a three-dimensional pore structure, high porosity and excellent electrochemical properties, which significantly improves the first charge and discharge efficiency of lithium-ion batteries and the capacity retention rate after 100 cycles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119581788A_ABST
    Figure CN119581788A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of diaphragm materials, and particularly relates to a superfine fiber composite battery diaphragm and a preparation method thereof. According to the prepared superfine fiber composite battery diaphragm, a PP melt-blown fiber material serves as a base material, the diaphragm is pretreated through a synchronous hot rolling-drafting technology to obtain a base membrane, then the base membrane is subjected to plasma treatment to improve the lyophilic performance of the base membrane, and finally cellulose acetate / beta-cyclodextrin / nano-hydroxyapatite serves as a finishing agent to prepare the superfine fiber composite battery diaphragm. And coating finishing is carried out on the fiber membrane to improve the pore diameter structure of the diaphragm, so that the affinity performance of the diaphragm to electrolyte is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of diaphragm materials, and in particular relates to an ultrafine fiber composite battery diaphragm and a preparation method thereof. Background Art

[0002] With the rapid development of industries such as consumer electronics, electric vehicles, and energy storage, batteries as the main energy storage devices have received great attention. As a key component of the battery, the diaphragm mainly isolates the positive and negative electrodes to prevent battery short circuits, and can also provide a shuttle channel for ions in the process of positive and negative electrode deintercalation. The pore structure, liquid absorption rate, and thermal dimensional stability of the diaphragm directly affect the internal resistance, capacity cycle performance, and safety performance of the battery.

[0003] At present, commercial diaphragm materials are mainly made of polypropylene or polyethylene as the main raw materials, and are prepared by dry and wet processes. Due to the limitations of the raw material properties, the prepared diaphragm has poor affinity for the electrolyte, which restricts the passage of lithium ions during the battery charging and discharging process and is not conducive to high-power charging and discharging. In addition, polyolefin materials have low thermal dimensional stability, and the diaphragm is prone to thermal shrinkage in a high temperature environment, causing battery short circuits and fire hazards. On the other hand, due to the processing method, the porosity of commercial polyolefin diaphragms is low, and the liquid absorption rate and liquid retention performance are poor, which restricts the battery's charge and discharge cycle performance and life. Commercial polyolefin diaphragms can no longer meet the requirements of the development and application of battery technology, and there is an urgent need to develop new diaphragm materials.

[0004] Fiber-based membrane materials are ideal potential lithium-ion battery separator materials due to their unique three-dimensional spatial mesh microporous structure. At present, the main processes for preparing fiber-based separator materials are electrospinning, wet nonwoven process and meltblowing. There are many studies on the preparation of lithium-ion battery separators by electrospinning and wet nonwoven processes, but there are still some shortcomings: the production efficiency of electrospinning nanofiber membranes is low, large-scale production is difficult and the mechanical properties are poor, which cannot meet the mechanical property requirements of the actual application of the separator. The thickness of the battery separator produced by the wet nonwoven process is too large and the porosity is not high. These shortcomings restrict its application as a separator in lithium batteries. The ultrafine fibers prepared by the meltblowing method can form small pores, high porosity and microporous structures, with good liquid absorption and liquid retention properties, which can meet the basic conditions of lithium-ion battery separators. However, due to its large pore size structure and uneven distribution, large thickness and poor mechanical properties, its application in lithium-ion battery separators is restricted. Summary of the invention

[0005] In view of the problems existing in the prior art, the present invention uses low-cost polypropylene melt-blown fiber material as a base material and prepares an ultra-fine fiber composite battery separator through finishing methods such as hot rolling, drawing, plasma and coating.

[0006] In one aspect, the present invention provides a method for preparing an ultrafine fiber composite battery separator, comprising: (1) Using PP meltblown fiber material as the base material, it is subjected to synchronous heat treatment and drafting treatment by two pairs of rotating hot rollers; (2) The fiber membrane is treated with low-frequency plasma to obtain an ultrafine fiber membrane substrate. The working principle is that the energetic plasma bombards the surface of the object, opens the covalent bonds of the surface structure, realizes the reorganization of the surface molecules, and thus achieves the purpose of modification, thereby improving the lyophilic properties of the fiber membrane; (3) Add the dried cellulose acetate (CA) and β-cyclodextrin (β-CD) polymers to N,N-dimethylformamide (DMF), heat in a water bath at 60°C, and stir with a magnetic force to prepare a clear and transparent solution with a mass fraction of 25-50%, which is the finishing solution; (4) adding nano-hydroxyapatite to the finishing liquid, performing ultrasonic treatment and high-speed stirring to fully disperse the nano-hydroxyapatite, to prepare a cellulose acetate / β-cyclodextrin / nano-hydroxyapatite composite finishing liquid; (5) coating the ultrafine fiber separator substrate with a cellulose acetate / β-cyclodextrin / nano-hydroxyapatite composite finishing liquid and drying the coating; and (6) The dried coated diaphragm is calendered.

[0007] In some embodiments, the fiber diameter of the PP meltblown fiber material is less than 2 microns and the gram weight is 15-25 g / m 2 .

[0008] In some embodiments, in step (1), the temperature of the first pair of rollers is 80-100°C, the temperature of the second pair of rollers is 135-160°C, the pressure of the two pairs of rollers is 10-15 MPa, and the fiber membrane is stretched by adjusting the rotation speed of the two pairs of rollers, and the stretching multiple is 1.05-1.25 times.

[0009] In some embodiments, in step (2), the plasma treatment time is 100-300 seconds, and the intensity is 30-150 watts to obtain an ultrafine fiber membrane substrate.

[0010] In some embodiments, in step (3), the weight of β-CD accounts for 5-40% of the weight of the finishing solution.

[0011] In some embodiments, in step (4), the nano-hydroxyapatite accounts for 3-8% of the total mass of cellulose acetate and β-cyclodextrin.

[0012] In some embodiments, in step (5), the coating thickness is 20-200 μm.

[0013] In some embodiments, in step (6), the calendering pressure is 5-15 MPa.

[0014] In a second aspect, the present invention provides an ultrafine fiber composite battery separator obtained by the above-mentioned preparation method.

[0015] In some embodiments, the ultrafine fiber composite battery separator has a three-dimensional pore structure, high porosity, a liquid absorption rate of up to 464.6%, an ionic conductivity of 1.64 mS / cm, and excellent electrochemical performance.

[0016] In a third aspect, the present invention provides a lithium-ion battery comprising the above-mentioned ultrafine fiber composite battery separator.

[0017] In some embodiments, the lithium-ion battery has an initial charge and discharge coulombic efficiency of 92.2%-96.7%, and a capacity retention rate of 98.1%-98.3% after 100 cycles.

[0018] Beneficial Effects The ultrafine fiber composite battery separator prepared by the present invention uses PP melt-blown fiber material as a substrate, pre-treats the separator through a synchronous hot rolling-drawing process to obtain a base membrane, then performs plasma treatment on the base membrane to improve its lyophilic properties, and finally uses cellulose acetate / β-cyclodextrin / nanohydroxyapatite as a finishing agent to coat the fiber membrane to improve the pore structure of the separator, thereby further improving the separator's affinity for the electrolyte. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 The SEM image of the ultrafine fiber composite battery separator prepared in Example 1 of the present invention is shown.

[0021] Specific embodiment In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.

[0022] Example 1 The base material is PP meltblown fiber material with an average fiber diameter of less than 2 microns and a gram weight of 20g / m².

[0023] It is heat treated and stretched synchronously by two pairs of rotating hot rollers: The parameter settings of the two pairs of rollers are as follows: the temperature of the first pair of rollers is 90°C, the temperature of the second pair of rollers is 140°C, the pressure of the two pairs of rollers is 10MPa, and the draft ratio is 1.15 times.

[0024] The fiber membrane was treated with low-frequency plasma, with a plasma treatment time of 150 seconds and an intensity of 80 watts.

[0025] The dried cellulose acetate and β-cyclodextrin polymer were added to N,N-dimethylformamide, heated in a water bath at 60°C, and stirred magnetically to prepare a clear and transparent solution with a mass fraction of 40%, which is the finishing solution, wherein the weight of β-CD accounts for 40% of the weight of the finishing solution.

[0026] Nano-hydroxyapatite was added to the finishing liquid, accounting for 5% of the total mass of cellulose acetate and β-cyclodextrin, and fully dispersed by ultrasonic and high-speed stirring to prepare cellulose acetate / β-cyclodextrin / nano-hydroxyapatite composite finishing liquid.

[0027] The ultrafine fiber diaphragm substrate is coated with a coating thickness of 80 μm and dried.

[0028] The dried coated diaphragm is calendered at a pressure of 10 MPa.

[0029] Example 2 The base material is PP meltblown fiber material with an average fiber diameter of less than 2 microns and a gram weight of 15g / m².

[0030] It is heat treated and stretched synchronously by two pairs of rotating hot rollers: The parameter settings of the two pairs of rollers are as follows: the temperature of the first pair of rollers is 80°C, the temperature of the second pair of rollers is 150°C, the pressure of the two pairs of rollers is 13MPa, and the draft ratio is 1.1 times.

[0031] The fiber membrane was treated with low-frequency plasma, with a plasma treatment time of 200 seconds and an intensity of 100 watts.

[0032] The dried cellulose acetate and β-cyclodextrin polymer were added to N,N-dimethylformamide, heated in a water bath at 60°C, and magnetically stirred to prepare a clear and transparent solution with a mass fraction of 35%, which is the finishing solution, wherein the weight of β-CD accounts for 30% of the weight of the finishing solution.

[0033] Nano-hydroxyapatite was added to the finishing liquid, accounting for 3% of the total mass of cellulose acetate and β-cyclodextrin, and fully dispersed by ultrasonic and high-speed stirring to prepare cellulose acetate / β-cyclodextrin / nano-hydroxyapatite composite finishing liquid.

[0034] The ultrafine fiber diaphragm substrate is coated with a coating thickness of 20 μm and dried.

[0035] The dried coated diaphragm is calendered at a pressure of 5 MPa.

[0036] Example 3 The base material is PP meltblown fiber material with an average fiber diameter of less than 2 microns and a gram weight of 22g / m².

[0037] It is heat treated and stretched synchronously by two pairs of rotating hot rollers: The parameter settings of the two pairs of rollers are as follows: the temperature of the first pair of rollers is 95°C, the temperature of the second pair of rollers is 135°C, the pressure of the two pairs of rollers is 12MPa, and the draft ratio is 1.2 times.

[0038] The fiber membrane was treated with low-frequency plasma, with a plasma treatment time of 100 seconds and an intensity of 100 watts.

[0039] The dried cellulose acetate and β-cyclodextrin polymer were added to N,N-dimethylformamide, heated in a water bath at 60°C, and stirred magnetically to prepare a clear and transparent solution with a mass fraction of 25%, which is the finishing solution, wherein the weight of β-CD accounts for 20% of the weight of the finishing solution.

[0040] Nano-hydroxyapatite was added to the finishing liquid, accounting for 6% of the total mass of cellulose acetate and β-cyclodextrin, and fully dispersed by ultrasonic and high-speed stirring to prepare cellulose acetate / β-cyclodextrin / nano-hydroxyapatite composite finishing liquid.

[0041] The ultrafine fiber diaphragm substrate is coated with a coating thickness of 150 μm and dried.

[0042] The dried coated diaphragm is calendered at a pressure of 12 MPa.

[0043] Example 4 The base material is PP meltblown fiber material with an average fiber diameter of less than 2 microns and a gram weight of 25g / m².

[0044] It is heat treated and stretched synchronously by two pairs of rotating hot rollers: The parameter settings of the two pairs of rollers are as follows: the temperature of the first pair of rollers is 100°C, the temperature of the second pair of rollers is 160°C, the pressure of the two pairs of rollers is 15MPa, and the draft ratio is 1.05 times.

[0045] The fiber membrane was treated with low-frequency plasma, with a plasma treatment time of 300 seconds and an intensity of 30 watts.

[0046] The dried cellulose acetate and β-cyclodextrin polymer were added to N,N-dimethylformamide, heated in a water bath at 60°C, and stirred magnetically to prepare a clear and transparent solution with a mass fraction of 50%, which is the finishing solution, wherein the weight of β-CD accounts for 5% of the weight of the finishing solution.

[0047] Nano-hydroxyapatite was added to the finishing liquid, accounting for 8% of the total mass of cellulose acetate and β-cyclodextrin, and fully dispersed by ultrasonic and high-speed stirring to prepare cellulose acetate / β-cyclodextrin / nano-hydroxyapatite composite finishing liquid.

[0048] The ultrafine fiber diaphragm substrate is coated with a coating thickness of 200 μm and dried.

[0049] The dried coated diaphragm is calendered at a pressure of 15 MPa.

[0050] Comparative Example 1 The same PP meltblown fiber material substrate as in Example 1 was used, but the heat treatment and stretching treatment by two pairs of hot rollers were not performed, and the plasma treatment was performed directly, and the parameters were the same as in Example 1. The subsequent steps were the same as in Example 1.

[0051] Comparative Example 2 The same substrate as in Example 2 was subjected to the hot roller treatment and the stretching treatment, but was not subjected to the plasma treatment.

[0052] The remaining steps are consistent with Example 2.

[0053] Comparative Example 3 The substrate of Example 3 was treated, and β-cyclodextrin was not added when preparing the composite finishing liquid. The other steps were the same as those of Example 3.

[0054] Comparative Example 4 The substrate was treated as in Example 4, but no nano-hydroxyapatite was added to the composite finishing solution. The remaining operations were the same as in Example 4.

[0055] Experimental Example 1 Battery assembly and testing: 1. Cut the diaphragm into a disc with a diameter of 19 mm, cut the disc with one side coated with lithium iron phosphate into a disc with a diameter of 16 mm as the positive electrode, and take a circular lithium sheet with a diameter of 16 mm as the negative electrode. First put the positive electrode and diaphragm into the CR2032 battery shell, then add a certain amount of 1 mol / L lithium hexafluorophosphate ethylene carbonate, diethyl carbonate, methyl ethyl carbonate (volume ratio 1:1:1) solution, finally place the negative electrode, stainless steel gasket and shrapnel and package them to assemble the battery. The whole process is completed in a glove box filled with argon.

[0056] 2. Battery cycle performance test: The prepared lithium battery was subjected to a charge and discharge cycle test under 1C conditions.

[0057] 3. Tensile strength test: The diaphragm was cut into 20×50 mm specimens and tested on an INSTRON 5982 universal material testing machine with a clamping distance of 20 mm and a tensile speed of 10 mm / min.

[0058] 4. Ionic conductivity test: The diaphragm was sandwiched between two stainless steel sheets, and the electrolyte was added to form a test cell. On the CHI660e electrochemical workstation, an AC impedance polarity test was performed with a scanning frequency range of 1-105 Hz and an amplitude of 5 mV.

[0059] 5. Liquid absorption rate test: After drying, immerse a certain mass of the diaphragm in 1 mol / L lithium hexafluorophosphate electrolyte for 2 h, use filter paper to absorb the electrolyte on the surface of the sample, and no electrolyte is precipitated within 10 seconds. Weigh the diaphragm to determine the wet weight, liquid absorption rate = (diaphragm wet weight - diaphragm dry weight) / diaphragm dry weight × 100%.

[0060] The test results are shown in Table 1.

[0061] Table 1 like Figure 1 As shown, the ultrafine fiber composite battery separator of the present invention has a three-dimensional pore structure, high porosity, high liquid absorption rate, excellent electrochemical performance, and can effectively improve the performance of the battery. By comparing the examples and comparative examples, it can be seen that each step in the preparation method of the present invention has an important influence on the performance of the battery separator.

[0062] Using a specific PP melt-blown fiber material as the substrate, after heat treatment and drawing treatment, the strength and uniformity of the fiber membrane can be improved. Plasma treatment increases the polar groups on the surface of the fiber membrane, improving the affinity of the diaphragm with the electrolyte and the coating. The use of cellulose acetate / β-cyclodextrin / nanohydroxyapatite composite finishing liquid further regulates the three-dimensional pore structure of the diaphragm and improves the liquid absorption rate of the diaphragm. The unique microporous structure of β-cyclodextrin and the rich polar functional groups of nanohydroxyapatite can effectively improve the electrochemical properties and thermal stability of the diaphragm. Calendering finishing further improves the flatness and mechanical strength of the battery diaphragm and improves the interface performance between the diaphragm and the electrode.

[0063] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A method for preparing a superfine fiber composite battery separator, comprising: (1) Using PP meltblown fiber material as the base material, it is subjected to synchronous heat treatment and drafting treatment by two pairs of rotating hot rollers; (2) treating the fiber membrane with low-frequency plasma to obtain an ultrafine fiber membrane substrate; (3) adding the dried cellulose acetate and β-cyclodextrin polymer into N,N-dimethylformamide, heating in a water bath at 60° C., and magnetically stirring to prepare a clear and transparent solution with a mass fraction of 25-50%, which is the finishing solution; (4) adding nano-hydroxyapatite to the finishing liquid, performing ultrasonic treatment and high-speed stirring to fully disperse the nano-hydroxyapatite, to prepare a cellulose acetate / β-cyclodextrin / nano-hydroxyapatite composite finishing liquid; (5) coating the ultrafine fiber separator substrate with a cellulose acetate / β-cyclodextrin / nano-hydroxyapatite composite finishing liquid and drying the coating; and (6) The dried coated diaphragm is calendered.

2. The preparation method according to claim 1, wherein The fiber diameter of the PP melt-blown fiber material is less than 2 microns and the gram weight is 15-25 g / m 2 .

3. The preparation method according to claim 1, wherein In step (1), the temperature of the first pair of rollers is 80-100°C, the temperature of the second pair of rollers is 135-160°C, the pressure of the two pairs of rollers is 10-15 MPa, and the fiber membrane is stretched by adjusting the rotation speed of the two pairs of rollers, and the stretching ratio is 1.05-1.25 times.

4. The preparation method according to claim 1, wherein In step (2), the plasma treatment time is 100-300 seconds and the intensity is 30-150 watts.

5. The preparation method according to claim 1, wherein In step (3), the weight of β-CD accounts for 5-40% of the weight of the finishing solution.

6. The preparation method according to claim 1, wherein In step (4), the nano-hydroxyapatite accounts for 3-8% of the total mass of cellulose acetate and β-cyclodextrin.

7. The preparation method according to claim 1, wherein In step (5), the coating thickness is 20-200 μm.

8. The preparation method according to claim 1, wherein In step (6), the calendering pressure is 5-15 MPa.

9. An ultrafine fiber composite battery separator obtained by the preparation method according to any one of claims 1 to 8. 10 . A lithium ion battery comprising the ultrafine fiber composite battery separator according to claim 9 .